Epidemiology and antibiotic susceptibility in anaerobic bacteraemia a 15-year retrospective study in South-Eastern Hungary - Sárvári Károly Péter; Rácz Nóra Bernadett; Burián Katalin (2022)
Introduction Bloodstream infections are considered as important factors of morbidity and represent a remarkable number of death, especially in developed countries. Methods In a 15-year retrospective study in the South-Eastern region of Hungary, the microbiological results of anaerobic blood culture (BC) bottles were analysed. The incubation of BCs was performed in the automated incubation system, and the isolates were cultured in an anaerobic chamber. The identification of the isolates was based on their biochemical profile (2004-2012) and mass spectrometry analyses (2013-2018). Antibiotic susceptibility testing was performed with minimal inhibitory concentration gradient diffusion method. Results The majority of the samples were submitted by the Department of Internal Medicine (37.7%), Intensive Care Unit (31.6%) and the Emergency Department (16.4%), and the number of strict anaerobic isolates per year showed an increasing tendency throughout the study. More than half of the isolates were Cutibacterium acnes (54.4%), but this bacterium was considered as a contaminant. The most frequent species upon Cutibacterium acnes were Bacteroides fragilis (9.2%), Clostridium perfringens (6.4%), other Clostridium species (4.8%), other Cutibacterium species (3.5%) and other Bacteroides species (2.5%). Penicillin, amoxicillin/clavulanic acid, imipenem, clindamycin, metronidazole and tigecyclin were very effective against Bacteroides fragilis, Clostridium perfringens, Fusobacterium nucleatum, Gemella morbillorum, Parvimonas micra and Eggerthella lenta strains. Conclusion We performed a 15-year period, retrospective investigation in South-Eastern Hungary with the participation of more than 1000 patients. The results of antibiotic susceptibility tests are in line with previous reports in the literature, and the results from the different geographical regions of the world suggest similar resistance mechanisms.
Keywords: Klinikai orvostan